The Utilization of Military Lifetime Health Record - Ahmad Firdause, Md Fadzil; Sallehudin, H; Bakar, N.A.A; Ismail, M; Razak, R.C; Baker, R (2019)
With the growth of IT, a comprehensive electronic health record system for the Malaysian armed forces is a must. However, because of the low success rate in the use of electronic health record systems, it is important to identify user acceptance factors for the systems. Thus, a research model that is grounded in TAM and UTAUT is developed to identify user adoption factors for Malaysian Armed Forces Hospital and Clinics to ensure the significant success of Military Lifetime Health Record (MLHR) implementations. A self-administered survey technique is employed and useful responses collected from users (military clinicians and medical personnel). The research model was then tested using the partial least square (PLS) technique. The results of this study confirm that behavioral intention is significant to actual usage of MLHR system by military clinician and medical personnel. Except of effort expectancy, all four () factors namely performance expectancy, social influence, facilitating condition and computer self-efficacy positively affect the military clinicians and medical personnel's intention to use the MLHR system. This study confirms that performance expectancy, social influence, facilitating condition and computer self-efficacy drive users' behavioral intention toward MLHR system usage. Having a clear understanding of what and how these determinants influence military clinician and medical personnel' behavioral intention is important as it can help make MLHR systems the main source of module when it comes to the next level HIS project for MAF.